Digital Land Certificates and Legal Objectives: An Empirical Study of Justice, Certainty, and Utility in Indonesia - Norma Fitria; Trinah Asi Islami; Muhammad Dzikirullah H. Noho; Ahmad Faruq; Ita Rahmania Kusumawati; Ahmad 'Ubaydi Hasbillah; M. Fahrudin Andriyansyah (Bulletin of Community Engagement, 2026)
Land ownership in Indonesia faces persistent challenges including disputes, overlapping claims, and document forgery, prompting the government to implement electronic land certificates through Ministerial Regulation ATR/BPN No. 3/2023 as a digitalization strategy to enhance legal certainty and administrative efficiency. This empirical juridical study examines the implementation of electronic land certificates in Jombang Regency and evaluates their contribution to achieving the legal objectives of justice, legal certainty, and utility (maslahah mursalah) using in-depth interviews, direct observation, and document analysis analyzed through Gustav Radbruch's legal objectives theory. The findings reveal that implementation operates through two mechanisms—new land title registration (12-19 days) and media transfer conversion (2-3 hours)—with substantial legal certainty achieved through centralized database architecture evidenced by zero reported land mafia cases; however, justice and utility objectives were unevenly realized, as demonstrated by urban-rural satisfaction gaps (4.1/5.0 versus 3.4/5.0), infrastructure constraints in remote sub-districts, and digital literacy barriers requiring intensive officer assistance for 55% of rural applicants. The study concludes that electronic certificates demonstrate conditional success in achieving legal objectives, with efficiency and security gains accompanied by "regressive utility" effects that advantage privileged populations, necessitating targeted infrastructure investment, sustained human resource development, and hybrid service models to prevent technology-enabled exclusion and realize the transformative potential of land administration digitalization.